Investigation of the RBC Potassium Polymorphism in the Indian Sheep - Adhikari, Alka; Mehta, S.P.S. (Asian Journal of Chemistry, 2016)
Two distinct K-types of animals, viz., high potassium (HK) and low potassium (LK), were identified in the Indian Bikaneri sheep. 52.6 were HK type and 47.4% were LK type. The metabolite concentrations in both types of animals were estimated and a comparison of the constituents was done statistically.